Clinical Characteristics and Outcome Analysis of 94 Children With Brain Abscess in Beijing: A Single-center Retrospective Study. Issue 2 (9th October 2020) - Dou, Zhen-Zhen; Guo, Ling-Yun; Liu, Lin-Lin; Li, Mu-Han; Hu, Hui-Li; Hu, Bing; Guo, Xin; Chen, Tian-Ming; Chen, He-Ying; Ge, Ming; Qian, Su-Yun; Zheng, Hu-Yong; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: There are limit studies about pediatric brain abscess in China. The aim of this study was to analyze clinical characteristics and outcomes of pediatric brain abscess in recent years in China. Methods: The clinical information of children with brain abscess hospitalized in Beijing Children's Hospital between January 1, 2007 and December 31, 2016 were retrospectively reviewed. Results: Ninety-four children were enrolled in this study. A Streptococcus milleri group (13.8%) was identified as the most common causative organisms, followed by Staphylococcus aureus (6.4%). The overall mortality was 21.6%, with 50.0% of deaths happening in the first week after diagnosis. Long-term outcomes of 74 patients were assessed with Glasgow Outcome Scale–Extended Pediatric Reversion: 50 patients with a score of 1–2 (favorable outcome) and 24 patients with a score of 3–8 (unfavorable outcome). Patients with multiple abscesses ( P = 0.029) and intraventricular rupture of brain abscess/hydrocephalus ( P = 0.024) had higher risk of unfavorable outcomes. Conclusions: Brain abscess is a serious disease with high mortality in children; more aggressive treatments should be considered in the first week of diagnosis because of high risk of death, and for patients with multiple brain abscesses and intraventricular rupture of brain abscess/hydrocephalus because of their higher risk of unfavorable.